Methodology of Teaching Qiraat Sab'ah: An Analysis of KH Muhsin Salim's Approach in the Context of Qur'anic Education: Metodologi Pengajaran Qiraat Sab'ah: Analisis Pendekatan KH Muhsin Salim dalam Konteks Pendidikan Al-Qur'an - Anami, Ami Muftil; Fasya, Ali (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: The science of qiraat began to develop since the time of the Prophet Muhammad. In 1911, qiraat science was introduced in Indonesia by KH Moenawwir after studying in the Middle East. In Jakarta, the science of qiraat sab'ah was spread by KH Muhsin Salim, who learned from Shaykh Abdul Qadir Abdul Adzim Abdul Barri. This study aims to explore KH Muhsin Salim's method in implementing the science of qiraat sab'ah and how he regenerated his students into qiraat experts. Methodology: This study used a qualitative approach with observation, interview, and literature analysis methods. Data were collected from various sources, including books, articles, and interviews with KH Muhsin Salim's students as well as direct observation at Qur'anic education institutions that he founded or taught. Main findings: KH Muhsin Salim used the talaqqi bi al-naẓor method which allowed students to read the Qur'an from writing in the presence of the teacher. This method is considered more practical and allows the spread of qiraat knowledge in Jakarta and its surroundings. Involvement: New insights into effective ways of teaching qiraat sab'ah in the context of modern education as well as KH Muhsin Salim's role in establishing and developing Qur'anic educational institutions. Conclusion: The fundamental role of K.H Muhsin Salim in teaching Qiraat science in the context of modern education using certain methods is a new offer in the context of developing and teaching qira'at science